Pariwisata Sebagai Faktor Pendukung Kesejahteraan Masyarakat - Firman Syah (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
The ideals of the Indonesian people are very noble and prioritize the interests of the community. This concept is the initial foothold from the government, namely Article 33 of the 1945 Constitution. This means that citizens are an important part of tourist destinations. On this basis, the idea was born that tourism is a supporting factor for community welfare. This research activity uses qualitative methods. The results of research in the field that tourism that tourism program that can support the welfare of the community is the cooperation and coordination between the government and the community. Because the largest area is rural, the tourism sector can enter the countryside. The tourism model can be in the form of managed natural resources such as adventure tourism, agro tourism, marine tourism, culinary tourism, cultural and historical tourism, and creative tourism.